Essential academic skills - Ireland, Lynette; Krenus, Brenda; Pointon, Leigh (Oxford University Press, 2008)
Provides a comprehensive guide to the skills required for successful completion of a university degree. Using a step-by-step approach it introduces students to core skills such as reading, writing, group work and exams. Activities throughout the chapters enhance each step of the learning process